The Morphology Aspect of The Quranic Recitation That Influence Islamic Laws in Tafseer Ayat Al-Ahkam By Al-Sabuniy - Rahim Ahmad, Abdul; Hussin, Hayati; Hafiz Saleh, Muhammad (International Journal of Engineering and Technology, 2018)
The Quranic recitation has a strong connection with the linguistics, especially in terms of the morphology. In fact, Islamic scholars frequently have different insights in terms of the implications of a sentence or a word with the same pronunciation and spelling, in general, the different forms of recitation of the morphological dimension will significantly affect all of the aspects. This study is aimed to divulge the morphological aspect in the book of Tafseer Ayat Al-Ahkam written by al-Sabuniy. A review was conducted in order to observe how far the differences towards the word construction with the same meaning could affect Islamic laws. If so, what kind of law does it apply to? The cause that affected it will be assessed cautiously. The methodology used in this study is a qualitative method. The main instrument in this study is based on the interpretation in the book of Tafseer Ayat Al-Ahkam by al-Sabuniy. The data collection in the form of words is analyzed inductively. As a result, it is discovered that there are also several differences of the Quranic verses in terms of the morphology, but not all of it leads towards different Islamic laws. In this book, there are nine morphological differences that lead towards the different meanings and laws. Most of them are focusing on fiqh and ibadah, whereas the rest are focusing on akidah and akhlak. This kind of research holds positive implications, as a foundation to the morphological studies on the work of other scholars.Â Â